2013
DOI: 10.9790/0853-1111720
|View full text |Cite
|
Sign up to set email alerts
|

A case of Inherited Unconjugated Hyperbilirubinemia foran incidental surgery: Anesthetic management and Review

Abstract: Congenital indirecthyperbilirubinemiaoccurs due to the relative deficiency or absence of the primary conjugating enzyme uridinediphosphate-glucuronyltransferase.The enzyme UDP glucuronyltransferase is responsible for the conjugation of bilirubin in liver. The enzyme is also essential for transport of many other substrates including drugs, hormones, toxins and neurotransmitters. Thus, anaesthetic management of such a case is quite challenging. Avoiding drugs which use this enzyme for its metabolism or excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The study revealed that serum unconjugated bilirubin concentration was significantly high among normal blood donors. Asymptomatic jaundice can be exacerbated following prolonged fasting, surgery and excessive alcohol consumption (Namasivayam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that serum unconjugated bilirubin concentration was significantly high among normal blood donors. Asymptomatic jaundice can be exacerbated following prolonged fasting, surgery and excessive alcohol consumption (Namasivayam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%